"Exon-shuffling" maps control of antibody- and T-cell-recognition sites to the NH2-terminal domain of the class II major histocompatibility polypeptide A beta. - Germain, R N (1985)
To investigate the role of the highly polymorphic amino-terminal (beta 1) domain of the class II major histocompatibility polypeptide A beta during recognition by T cells and antibodies, "exon-shuffling" was carried out between genomic recombinant DNA clones of Ak beta and Ad beta to generate a hybrid gene containing Ak beta exons for the amino-terminal domain followed by the Ad beta exons for the remainder of the molecule. L-cell gene transfectants expressing this hybrid A beta gene in combination with Ak alpha were compared to L cells expressing wild-type Ak beta Ak alpha dimers in tests of antigen-presentation to T-cell clones and hybridomas and for staining by a panel of anti-I-Ak-specific monoclonal antibodies. These antibodies were also tested for their reactivity with a B-lymphoma transfectant expressing Ak beta in the absence of Ak alpha. The results showed no qualitative differences in either T-cell or antibody-mediated recognition of I-Ak molecules containing either the exon-shuffled or wildtype Ak beta. Together with the data involving the B cell transfectant expressing only Ak beta, these results map control of the A beta contribution to the immunologically relevant determinants of I-Ak to the highly polymorphic amino-terminal domain and indicate little, if any, contribution to allele-specific recognition by amino acid sequence variations in the remaining portions of the A beta polypeptide.